Investigating Managers’ Fine-Grained Evaluation Processes in Organizations: Exploring Two Dual-Process Perspectives - Sun, Haoye; Verbeke, Willem J. M. I.; Belschak, Frank; van Strien, Jan; Wang, Lei (Frontiers in Neuroscience, 2021)
The dual-process theory is a significant theory in both organizational theory and social psychology and two conjectures about this theory are considered in this paper; the default-interventionist versus parallel-competitive account. Our research goal is to empirically investigate these two views. In concrete terms, by using event-related potentials (ERPs), we seek to study the fine-grained brain processes and self-reported feelings involved in managers’ evaluations of target employees within an economic context (firing employees) versus a social network context (excluding employees). Using the stereotype content model (SCM) categories, each target employee has high (or low) warmth and high (or low) levels of competence. In the fine-grained ERP analysis of the brain process, we focus on three time windows of interest: novelty detection (N2) and goal violation detection (N400) at the unconscious level, and we then evaluate conscious emotional arousal (late positive potential, LPP). Finally, we focus on the self-reported feelings when having to fire or exclude target employees. As goal pursuit theory predicts, the brain dynamics and self-reported measures differ widely across the two organizational contexts; in concrete terms, processes at a later stage overrule early stages depending on the context. This implies that the data bespeaks more for the parallel-competitive account than the default-interventionist account. We discuss the implications of these findings for research in management and management practice.